A dataset of the operating station heat rate for 806 Indian coal plant units using machine learningZenodo - Yifu Ding; Jansen Wong; Serena Patel; Guiyan Zang; Dharik Mallapragada (Data in Brief)
India aims to achieve net-zero emissions by 2070 and has set an ambitious target of 500 GW of renewable power generation capacity by 2030. As of 2025, coal-based power generation accounts for approximately 47 % of the total capacity and >70 % of the total electricity generation. Upgrading and decarbonizing high-emission coal plants became a pressing energy issue. A key technical parameter in coal plant operations is the operating station heat rate (SHR), which represents the thermal efficiency during operation. Yet, the operating SHR of Indian coal plants varies and is not comprehensively documented. This study leverages existing databases to create a SHR dataset for 806 Indian coal plant units, utilizing machine learning (ML), and presents the most comprehensive coverage to date. Additionally, it incorporates environmental factors such as water stress risk and coal prices as predictive features to enhance accuracy. This dataset, accessible through our visualization platform, is designed to support energy and environmental policymaking as India advances toward its renewable energy objectives.